Investigating Experience of University Students in Using ChatGPT in English Learning Context - Ni Nyoman Risna Sari Devi; Made Hery Santosa; I Putu Indra Kusuma (English Education Department STKIP Agama Hindu Singaraja, 2025)
The integration of Artificial Intelligence (AI) in education, particularly generative tools like ChatGPT, has significantly reshaped how language learning is approached in higher education. However, while much has been said about the potential benefits of AI, there remains a lack of empirical research on students’ actual experiences. This study investigates the user experience (UX) of 110 English Language Education (ELE) students at Universitas in Bali using ChatGPT to support their English learning. The User Experience Questionnaire (UEQ) was employed to measure six key dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The results indicate that students perceived ChatGPT positively across all dimensions, especially in terms of ease of use, emotional engagement, and learning efficiency. Validity and reliability tests confirmed the robustness of the instrument. The findings highlight ChatGPT’s potential not only as a functional educational tool but also as a motivational and user-friendly platform. However, the study also underscores the need for digital literacy and ethical guidance to ensure responsible use. This research contributes to a more nuanced understanding of AI in language education and provides insights for educators and policymakers aiming to integrate AI meaningfully into curriculum design.